Nursing education research in Sub-Saharan Africa: A systematic review and bibliometric analysis. - Beth Waweru; Peter Gatiti; Serah Wachira (PLOS Digital Health)
Nursing education is pivotal for ensuring competent healthcare professionals, and its improvement is essential for enhancing the quality of health care systems globally. This study focuses on nursing education research in Sub-Saharan Africa (SSA) over the last decade, employing both bibliometric analysis and systematic review methodologies. The bibliometric analysis reveals an evolving landscape of nursing education research in SSA, offering insights into trends, key countries, journals, and predominant research themes. Notably, the study identifies a scarcity of literature using bibliometric approaches in nursing research, addressing this gap by providing a comprehensive overview of the field.The systematic review, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, explores 1359 articles published in the last ten years, focusing on nursing education in SSA. The analysis of 1288 selected articles emphasize experiences and challenges faced by nursing and midwifery students during their education and clinical training. The emerging themes cuts across classroom teaching, clinical learning environments, and overall clinical practice. The findings highlight the need for attention to educational support, effective communication, professionalism, inclusivity, and innovative teaching methods. Limitations include the exclusive focus on SSA, restricting generalizability to other regions. Nonetheless, the study offers valuable insights for educators, policymakers, and institutions to enhance the quality of nursing education. By addressing identified challenges, fostering innovation, and promoting inclusivity, stakeholders can better prepare students to meet the dynamic demands of the healthcare profession in SSA and potentially other regions, especially Low- and Middle-income Countries. The research contributes to the ongoing efforts to bridge the gap between nursing education theory and practice, ultimately improving healthcare outcomes in the region.